(untitled) (International Journal of Engineering and Computer Science, 2017)
Machining is a complex process in which many variables can deleterious the desired results. Among them, cutting tool vibration is the most critical phenomenon which influences dimensional precision of the components machined, functional behavior of the machine tools and life of the cutting tool. In a machining operation, the cutting tool vibrations are mainly influenced by cutting parameters like cutting speed, depth of cut and tool feed rate. The cutting tool vibration signals have been collected through a data acquisition system supported by RS-232 software. On mild steel, the collecting data at various parameters like depth of cut, speed, feed rate etc. A number of data have been recorded by varying the above parameters. On the completion of experimental work MATLAB has been used to analyze the result for vibration in metal cutting tool and also to predict the optimum behavior of the system under any cutting condition within the operating range.